Disk Array Models for Automating Storage Management. - Merchant, Arif (Communications of the ACM, 2009)
The article discusses another article in the issue which concerns the management of computing disk array storage related to the automation of storage management. Managing disk array storage is complex, the author states, as it involves tasks such as arranging for data backup, prioritising data access, and management decisions geared towards simplifying implementation.